Development of RF energy harvesting technique for Li-Fi application - Rosli, M.A. (Institute of Electrical and Electronics Engineers Inc., 2017)
This work aims to improve the power generation by applying and experimenting a new technique of Radio Frequency (RF) energy harvesting using products of Powercast. This energy is used to activate a Light-Fidelity (Li-Fi) sample device and charge an energy storage system simultaneously. The final outcome of the system is now able to activate the Li-Fi sample device and charge a battery system at the same time. With the project being improved on a wider scale, many power problems can be solved in such a way that will help all humankind. © 2016 IEEE.